Modeling WWOX Loss of Function in vivo: What Have We Learned? - Tanna, Mayur; Aqeilan, Rami I. (Frontiers in Oncology, 2018)
The WW domain–containing oxidoreductase (WWOX) gene encompasses a common fragile sites (CFS) known as FRA16D, and is implicated in cancer. WWOX encodes a 46kDa adaptor protein, which contains two N-terminal WW–domains and a catalytic domain at its C–terminus homologous to short–chain dehydrogenase/reductase (SDR) family proteins. A high sequence conservation of WWOX orthologues from insects to rodents and ultimately humans suggest its significant role in physiology and homeostasis. Indeed, data obtained from several animal models including flies, fish, and rodents demonstrate WWOX in vivo requirement and that its deregulation results in severe pathological consequences including growth retardation, post–natal lethality, neuropathy, metabolic disorders, and tumorigenesis. Altogether, these findings set WWOX as an essential protein that is necessary to maintain normal cellular/physiological homeostasis. Here, we review and discuss lessons and outcomes learned from modeling loss of WWOX expression in vivo.